The shadow of childhood harm behind prison walls: theory, evidence, and treatment - Wolff, Nancy L. (Oxford University Press, 2023)
Prison. Just the word alone conjures up images of harshness and negativity. While the word criminal summons feelings of fear, disgust, anger, aggression, and revenge. These near-universal feelings about criminals are the foundation of prisons as places where harm, through neglect, indifference, and disregard, festers and replicates like a virus. For this reason, any conversation about prison and its potential for anything other than harm must start with the people who live there. In 'The Shadow of Childhood Harm Behind Prison Walls', the author, Nancy Wolff, uses a balance of compassion and evidence to take readers through the lives of people who end up inside prison. Guided by the words of those who have lived the experience of harm, she weaves an expansive body of research that lays bare the harm that eventually led to incarceration.